Review of Randall Sandke. 2010. Where the Dark and Light Folks Meet: Race and the Mythology, Politics, and Business of Jazz. Lanham, Maryland: The Scarecrow Press - Gridley, Mark C. (Current Musicology, 2011)
Randall Sandke has written a new jazz history book. But it is not the usual jazz history. Rather than offering decade-by-decade accounts of different jazz styles, Where the Dark and Light Folks Meet offers facts that differ from popular understanding of the origins of jazz styles. It presents fresh perspectives on the ways that the music industry in the United States has treated jazz. Like other jazz histories, this one addresses the origins of jazz in New Orleans, what in the music is retained from Africa, the origins of modern jazz, and recent trends in jazz styles. But this volume overturns common wisdom about these topics. Instead of recounting traditional notions about jazz history, Sandke raises crucial questions about how jazz history has been told: What are the dangers of combining the telling of history with social activism? How have both black and white jazz musicians been negatively affected by stereotypes? Are the rhythmic approaches of jazz and African music fundamentally the same? Was the music in New Orleans’ Congo Square a decisive influence on jazz? Did Jim Crow laws actually affect the creation of jazz? When did white musicians begin playing jazz in New Orleans? Did big business dominate the jazz world in the past thirty years? Where the Dark and Light Folks Meet provides behind-the-scenes glimpses into the business of the jazz world, touching on audiences and presenters, studio work, copyrights, agents and managers, and the decline of major record companies in the age of the Internet. Sandke’s history of jazz is based on voluminous research, much of which is fresh. Instead of merely repeating the accounts of the best-known jazz historians, Sandke highlights their errors. Instead of celebrating the thinking of prominent jazz journalists, he identifies their biases. Where the Dark and Light Folks Meet boldly attacks jazz critics, and, quite understandably, jazz critics have attacked the book for this.